Thinking-for-speaking patterns in the L2 classroom: A mindful conceptual engagement approach to teaching motion events - Aguiló-Mora, Francisca; Negueruela-Azarola, Eduardo (Frontiers in Communication, 2022)
This participatory action research project explores how First Language (L1) Thinking-for-Speaking (TFS) patterns (Slobin, 1996) operate in Second Language (L2) communication. We center on L2 Spanish learners and the teaching/learning of motion events when asking-and-giving-directions. This is a communicative task placed at the intermediate level in the ACTFL proficiency guidelines (2012). It is conventionally taught in the second semester of study in Spanish L2 programs at North American universities. However, asking for and giving directions is conceptually quite challenging for L1 English advanced L2 Spanish courses even for Spanish majors at universities in North America. As documented in Aguiló Mora and Negueruela (2015), giving directions is conceptually complex because it is connected to motion events (Talmy 2000) and TFS patterns. This research illustrates a pedagogical intervention to teach motion events as conceptual categories in the Spanish L2 classroom. The goal is to implement instructional tasks that promote conceptual understanding, engagement, and internalization of a L2 conceptualization of motion so as to shift L1 TFS patterns. Such conceptual engagement tasks should enable L2 learners to appreciate how a different language expresses motion events and directions differently (Negueruela 2013). This type of conceptual instruction is quite specific. It requires the development of pedagogical materials for the teaching of motion events. It also starts with active and mindful engagement by L2 learners, so as to foster the creation of their own conceptual representations as learning tools to understand motion events. This is the basis for a Mindful Conceptual Engagement (MCE) approach. From an MCE perspective, the key to the shift in L1 TFS patterns is genuine conceptual and mindful engagement. Findings from a Sociocultural Theory (SCT) perspective illustrate that functional conceptual categories of meaning grow as they are mindfully applied.